EFFECT OF SERVICE QUALITY, RELIGIOSITY, RELATIONSHIP CLOSENESS, AND CUSTOMER TRUST ON CUSTOMER SATISFACTION AND LOYALTY AT BANK JATIM SYARIAH - Sapoetra D.B.; Basuki R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research aims to examine the effect of service quality, religiosity, relationship closeness, and customer trust on customer satisfaction and loyalty at Bank Jatim Syariah. Based on the literature review, the research hypothesis states that service quality and customer trust have a positive and significant effect on customer satisfaction. In addition, service quality, relationship closeness, customer satisfaction and religiosity have a positive and significant effect on customer loyalty. This research uses a questionnaire distributed to respondents/ active customers of Bank Jatim Syariah. The hypothesis testing was carried out using Structural Equation Model (SEM) analysis technique. The research findings showed that service quality and customer trust have a positive and significant effect on customer satisfaction, customer satisfaction and relationship closeness have a positive effect on customer loyalty, and service quality and religiosity have a positive and not significant effect on customer loyalty. In particular, this research shows that the religiosity factor that has been an added value for sharia banks to retain customers is no longer relevant. Based on the research findings, it is recommended that Bank Jatim Syariah evaluate the tangible, product, and service factors and implement sustainable service standards so that customer satisfaction and loyalty are maintained.